ANALISIS PRODUKTIVITAS TENAGA KERJA PADA PEKERJAAN FONDASI PEMBANGUNAN FASILITAS PENYIMPANAN PMI PROVINSI GORONTALO - Jumi, Jumiati Bandu; Tuloli, M. Yusuf; Utiarahman, Arfan (Composite Journal, 2023)
Labor productivity is one of the success factors of a project where the labor is directly involved in construction in the field. This study aims to know the level of labor productivity in the project for construction of PMI storage facility in Gorontalo Province. This study uses work sampling (productivity rating), which is a method that can be used to measure productivity easily to obtain the LUR (Labor Utilization Rate) value for each labor. This study is conducted by observing the productivity of 7 labors where the observation of productivity (LUR) is done for 22 days in each labor and the type of work observed is raft foundation work. The finding shows that the average labor productivity level in foundation work is 69.22% > 50°/». Thus, it can be concluded that the level of labor productivity in foundation work in the project for construction of the PMI storage facility in Gorontalo Province is quite productive and splendid. The avemge value of volume/labor is 0.163 m3 where its coefficient value in the field for excavation, soil compaction, workshop floor, formwork, and casting is higher than AHSP (Work Unit Price Analysis) 2016 whereas the value for reinforced bar and drainage reinforcement is higher.